Effective one-band models for the one-dimensional cuprate Ba2-xSrxCuO3+δ - Feiguin, A. E. (2023)
We consider a multiband Hubbard model Hm for Cu and O orbitals in Ba2-xSrxCuO3+δ similar to the three-band model for two-dimensional cuprates. The hopping parameters are obtained from maximally localized Wannier functions derived from ab initio calculations. Using the cell perturbation method, we derive both a generalized t-J model HtJ and a one-band Hubbard model HH to describe the low-energy physics of the system. HtJ has the advantage of having a smaller relevant Hilbert space, facilitating numerical calculations, while additional terms should be included in HH to accurately describe the multiband physics of Hm. Using HtJ and the density matrix renormalization group method, we calculate the wave-vector-resolved photoemission and discuss the relevant features in comparison with recent experiments. In agreement with previous calculations, we find that the addition of an attractive nearest-neighbor interaction of the order of the nearest-neighbor hopping shifts the weight from the 3kF to the holon-folding branch. Kinetic effects also contribute to this process.